Particular concerns with regard to the Rotterdam Rules - Alcántara González, José María; Hunt, Frazer; Johansson, Svante O.; Oland, Barry; Pysden, Kay; Ramberg, Jan; Schmitt, Douglas G.; Tetley C.M., William; Vidal, Julio (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
As the Rotterdam Rules signature process gains momentum, strong dissenting opinions are also starting to be heard. This article or manifesto sums up the collective critical voice of nine worldwide leading shipping lawyers and professors. It provides a short and precise analysis of the Rotterdam Rules main features from the point of view of those issues which the authors fi nd unworthy of praise. And their conclusion is that the Rotterdam Rules simply just add up more complexity to the present shipping and multimodal international regulation. The article closes with a quest for alternatives aimed to get the best of what we already have and opens the gate to proposals based on the updating and complementation of the regulation in force today.